The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.2.24586/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Predictive value of serum NGAL for the diagnosis of Delayed Graft Function in kidney transplantation

Abstract: Background and aims the role of serum neutrophil gelatinase-associated lipocalin (NGAL) in predicting delayed graft function (DGF) after kidney transplantation is poorly defined. The objective of this study was to evaluate the serum NGAL expression in the early postoperative phase after kidney transplantation and compare it with serum creatinine (Cr). Methods We studied 32 patients who received kidney transplantation from deceased (n=24) and live (n=5) donors during October 2017 to December 2018 at the Urology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These days, the genes that govern the acceptance or rejection of a transplant are at the center of attention. Several studies have shown that proteins, DNA, and RNA could be promising candidate biomarkers for monitoring renal transplantation rejection [ 3 , 4 , 5 , 6 , 7 ]. The putative genes that play a role in the survival of transplanted cells, tissues, or organs belong to a family called the major histocompatibility complex (MHC) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These days, the genes that govern the acceptance or rejection of a transplant are at the center of attention. Several studies have shown that proteins, DNA, and RNA could be promising candidate biomarkers for monitoring renal transplantation rejection [ 3 , 4 , 5 , 6 , 7 ]. The putative genes that play a role in the survival of transplanted cells, tissues, or organs belong to a family called the major histocompatibility complex (MHC) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%